Research and theory to foster change in the face of grand health care challenges - Hefner, Jennifer L.; Cross, Dori A.; Shay, Patrick D. (Emerald Publishing Limited, 2024)
This book contains an Open Access chapter. Healthcare organizations today face widespread change as they confront varied grand challenges in uncertain environments. Leaders in healthcare require a comprehensive understanding of effective approaches to organizational change, yet the theoretical and practical landscape is evolving rapidly. Volume 22 of Advances in Health Care Management focuses on environmental uncertainty and the responsiveness of health care organizations, the mechanisms of change and how leaders within organizations frame and execute change, and investigates organizational preparedness and response in the face of acute crisis. The authors highlight the key ways in which organizations must orient toward, and build adaptive resilience to weather, an environment of persistent uncertainty and change.
Includes index.
Keywords: Health services administration.; Organizational change.; Business & Economics -- Management.; Medical administration & management.; elektronické knihy; electronic books